Users’ Perceptions of Contextualized Reading Materials in Enhancing Reading Comprehension - Maria May A. Benosa; Joy Gaza (The Indonesian Institute of Science and Technology Research, 2026)
This study aimed to document the research-based reading interventions and innovations in improving reading competencies among Junior High School Students between 2013 and 2019. Specifically, it sought to answer the following objectives: describe the students’ perception of contextualized reading materials, and design a school-based policy to optimize the utilization of the Research-based interventions. This study used a descriptive research design and a mixed method to discuss and answer the objectives of this research. The respondents comprised one teacher who implemented the reading interventions and 15 students who utilized the interventions. Based on the study's results, the archived reading interventions focus on improving students' reading comprehension and English proficiency. Many studies conducted between 2013 and 2019 were designed to address the learners' needs. Each intervention proposed different strategies that could solve the timely concerns about reading. However, only the contextualization of reading materials was realized. It has proven effective and significantly improved reading comprehension since it was frequently utilized. The study showed a high level of engagement among the students with the contextualized reading materials and found them helpful in understanding them. Nevertheless, there were still competencies unsuitable for the student’s level. They find it difficult, and sometimes it is hard to understand. Some competencies are not appropriate for the grade level they are and need to provide alternative reading materials instead. Therefore, it is recommended that language teachers revise the reading materials based on the students' interests and level of appropriateness to improve reading comprehension, fill the students’ learning gap, and provide different levels of support and scaffolding to meet the needs of diverse learners. These results served as the basis for crafting the school-based policy on utilizing the reading interventions.